Optimasi Rasio Glukomanan dan Xanthan Gum terhadap Karakteristik Fisikokimia dan Sensoris Kukis Berbasis Tepung Bebas Gluten (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
Gluten-free flour-based cookie products face a major challenge in producing physicochemical and sensory characteristics equivalent to wheat-based products due to the absence of gluten as a structural component. One common approach to address this issue is the addition of hydrocolloids, such as glucomannan and xanthan gum. This study aims to systematically examine the effect of the ratio of glucomannan and xanthan gum on the texture characteristics, spreadability, and sensory properties of gluten-free flour-based chocolate cookies using the Systematic Literature Review (SLR) method. The literature search process was carried out on several scientific databases using keywords related to gluten-free cookies, glucomannan, xanthan gum, texture, spreadability, and sensory properties. Selected articles were selected based on inclusion and exclusion criteria, then analyzed and synthesized narratively with reference to the PRISMA guidelines. The results of the study indicate that xanthan gum tends to increase the hardness and structural stability of cookies, but can decrease spreadability and crispiness at high concentrations. Conversely, glucomannan plays a role in enhancing softness and mouthfeel through its high water-binding capacity, although it can potentially limit spreadability if used excessively. The combination of glucomannan and xanthan gum exhibits a synergistic effect in balancing textural characteristics and enhancing sensory acceptability. In conclusion, optimizing the ratio of glucomannan to xanthan gum is a key factor in developing gluten-free chocolate cookies with optimal physicochemical and sensory characteristics.